1995
DOI: 10.1017/s0317167100039445
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Functional Recovery Following Stroke

Abstract: This article reviews recent evidence from animal experiments indicating that there is considerable potential for reorganization of representations and functions in sensory and motor cortex following localized lesions or various manipulations of peripheral target structures. Three major mechanisms for this plastic reorganization are considered: unmasking of existing but functionally inactive pathways, sprouting of fibers from surviving neurons and formation of new synapses, and redundancy of CNS circuitry allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 39 publications
3
69
0
1
Order By: Relevance
“…This possibility is supported by various changes known to occur in distant areas after a central lesion (Chollet et al, 1991;Lee and van Donkelaar, 1995;Witte and Stoll, 1997;Nudo, 1999). Particularly, the premotor cortex has been suggested to play an active role in motor recovery after stroke in nonhuman primates (Liu and Rouiller, 1999;Frost et al, 2003) and humans (Miyai et al, 1999(Miyai et al, , 2002.…”
Section: Introductionmentioning
confidence: 95%
“…This possibility is supported by various changes known to occur in distant areas after a central lesion (Chollet et al, 1991;Lee and van Donkelaar, 1995;Witte and Stoll, 1997;Nudo, 1999). Particularly, the premotor cortex has been suggested to play an active role in motor recovery after stroke in nonhuman primates (Liu and Rouiller, 1999;Frost et al, 2003) and humans (Miyai et al, 1999(Miyai et al, , 2002.…”
Section: Introductionmentioning
confidence: 95%
“…The amount of dendritic growth in the undamaged motor cortex was associated with both lesion size and improved functional outcome. Neuronal reorganization within this region likely reflects unmasking and reorganization of ipsilateral corticospinal projections (Lee and van Donkelaar, 1995) or axonal sprouting and formation of novel subcortical projections (Kawamata et al, 1997;Chen et al, 2002;Papadopoulos et al, 2002). Although it is conceivable that recovery could be supported by the minimal ipsilateral (uncrossed) projections from the undamaged motor cortex to cervical spinal cord, it is more likely that the corticofugal sprouting from the undamaged motor cortex to the red nucleus (on the affected side) is contributing to improved function Papadopoulos et al, 2002).…”
Section: Early Rehabilitation (Er5) Does Not Exacerbate Infarct Size mentioning
confidence: 99%
“…After an ischemic attack, a majority of stroke patients exhibit certain levels of motor weakness and sensory disturbances; however, over time, most will show a certain degree of functional recovery [28,63]. The results of several animal and human studies on stroke have revealed that post stroke recovery and restoration of function may be explained by brain reorganization and brain plasticity [63,82,126,129]. As suggested by Lledo and colleagues [86], brain plasticity refers to the brain ability to change its structure and function during maturation, learning, environmental changes and pathology.…”
Section: Brain Plasticity and Post Stroke Recoverymentioning
confidence: 99%